An unlikely hero: the origins of affirmative action during the Nixon administration - Yuill, Kevin (2001)
The dissertation builds upon the question of why Nixon, a Republican, implemented the first affirmative action programs. It is divided into three parts. The first charts the liberal approach to race relations and the crisis that attended its collapse. As Habermas noted, a "legitimation crisis" affected private institutions necessitating a new round of government intervention. This section explores the idea that affirmative action was part of this legitimation crisis, an administrative replacement for the failure of the post-war hope that racism would disappear after the destruction of formal barriers to black equality.